Pancreatic Perivascular Epithelial Cell Tumor (PEComa) with Liver Metastasis: a Case Report and Literature Review - Yu. A. Stepanova; Kh. A. Ayvazyan; D. V. Kalinin; O. I. Zhavoronkova; V. S. Shirokov; A. V. Zhao (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Aim: to present a clinical case of pancreatic PEComa with liver metastases with an emphasis on morphological features, radiology diagnostic methods and features of treatment tactics, allowing practitioners to get an idea about this rare mesenchymal tumors composed of “perivascular epithelioid cells”, and a review of literature data on pancreatic PEComa, including 32 author's cases.General statements. A 22-year-old woman who was surgically treated for pancreatic head PEComa with infiltration of the duct of Wirsung, common bile duct, duodenal wall, focal invasion into the blood and lymphatic vessels, and perineural space infiltration. Synchronously, metastases were detected in both liver lobes, for which she took Everolimus for 6 years under the control of radiology methods with dose adjustment and frequency of administration. At the A.V. Vishnevsky National Medical Research Center of Surgery, the patient underwent right-sided hemihepatectomy and atypical resection of II-III liver segments.Conclusion. To determine clearer criteria for the diagnosis and differential diagnosis of PEComa, to identify criteria for the malignancy of these tumors, to develop treatment tactics and further dynamic monitoring, a set of statistical data of significant group and randomized clinical trials are needed. Pancreatic PEComas in this group are extremely rare and often have a benign course. The presented clinical case demonstrates the most malignant form of this tumor with localization in the pancreas and liver metastases.